Barthes’ words - Marinas, José Miguel (Escritura e Imagen, 2021)
This article takes a tour of the main motives and concepts of Roland Barthes’ intellectual trajectory. Faced with the more classical and habitual reading of them, the work detects in them a method of discovery that is made of displacements and abandonments of the conventional that go much further than any “structuralist” approach.